1978
DOI: 10.1111/j.1365-3083.1978.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐D Restriction of the Macrophage‐Dependent Response of Immune Human T Lymphocytes to PPD in Vitro: Inhibition by Anti‐HLA‐DR Antisera

Abstract: The response of T cells from sensitized individuals to low doses of PPD in vitro is macrophage-dependent. By testing different allogeneic combinations of macrophages and T lymphocytes, it was found that an optimal response required that antigen be presented by macrophages sharing at least one of the HLA-D determinants of the T cell donor. Antisera recognizing HLA-A, -B or -DR antigens were found to be able to inhibit this proliferative response. The anti-HLA-DR antisera were found to exert their inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 28 publications
9
50
0
Order By: Relevance
“…In the human, HLA-A-or -B-locus homology requirements between killer and target cells have been reported for cytotoxic responses generated against the Y male antigen (13), influenza-infected cells (14,15), and hapten-modified cells (16,17). In contrast, we and others have reported the importance of HLA-D-region determinants in the generation of human proliferative responses to haptens and other conventional antigens (18)(19)(20)(39)(40)(41). In this study we have found that antigen presentation requirements for induction of cells capable of cytotoxic effector function also differ from those for proliferative responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human, HLA-A-or -B-locus homology requirements between killer and target cells have been reported for cytotoxic responses generated against the Y male antigen (13), influenza-infected cells (14,15), and hapten-modified cells (16,17). In contrast, we and others have reported the importance of HLA-D-region determinants in the generation of human proliferative responses to haptens and other conventional antigens (18)(19)(20)(39)(40)(41). In this study we have found that antigen presentation requirements for induction of cells capable of cytotoxic effector function also differ from those for proliferative responses.…”
Section: Resultsmentioning
confidence: 99%
“…Available data suggest that the proliferative responses in vitro are related in magnitude and specificity to delayed hypersensitivity reactions (49)(50)(51). Investigations of both proliferative responses to hapten-conjugated cells (18)(19)(20) and to purified protein derivative (39)(40)(41) suggest that the autologous determinants involved in delayed hypersensitivity reactions are encoded in the HLA-D region. Haptenic determinants on soluble proteins or membrane fragments (52) …”
Section: Resultsmentioning
confidence: 99%
“…It is a somewhat unexpected finding that free mannan alone could specifically bind T lymphocyte membranes because it has previously been demonstrated that the T cell receptor is specific for antigen associated with a MHC product (8)(9)(10)(11)(12). Such an association is indeed required for mannan inasmuch as monocyte-T lymphocyte interactions in mannan-induced T cell responses are HLA class II-restricted (32 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Research performed on murine or human models has suggested direct binding of antigen alone onto primed T cells (1)(2)(3)(4)(5)(6)(7). However, most reports have shown that T lymphocytes recognize the antigen in association with a major histocompatibility complex (MHC)' product, and not alone (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary experiments with purified populations of monocytes and lymphocytes, we have found the monocyte to be the site ofinhibition ofthe procoagulant response by this monoclonal anti-HLA-DR antibody. The use of [3H]thymidine uptake by immune T cells has shown that the antigen presentation step is interfered with by anti-HLA-DR antisera (36). We have recently described a PPD reactive human T cell clone that mediates the procoagulant response to PPD presented by autologous monocytes (39).…”
Section: Discussionmentioning
confidence: 99%